State of the Climate in 2020 - Blunden, J.; Boyer, T.; Grooss, Jens-Uwe; Müller, Rolf (Bulletin of the American Meteorological Society, 2021)
In 2020, the dominant greenhouse gases stored in Earth’s atmosphere continued to increase. The annual global average carbon dioxide (CO2) concentration at Earth’s surface was 412.5 ± 0.1 ppm, an increase of 2.5 ± 0.1 ppm over 2019, and the high-est in the modern instrumental record and in ice core records dating back 800,000 years. While anthropogenic CO2 emissions were estimated to decrease around 6%–7% globally during the year due to reduced human activities during the COVID-19 pan-demic, the reduction did not materially affect atmospheric CO2 accumulation as it is a relatively small change, less even than interannual variability driven by the terrestrial biosphere. The net global uptake of ~3.0 petagrams of anthropogenic carbon by oceans in 2020 was the highest in the 39-year record and almost 30% higher than the 1999–2019 average. Weak El Niño-like conditions in the eastern equatorial Pacific Ocean in early 2020 cooled and transitioned to a moderate La Niña later in the year. Even so, the annual global surface tem-perature across land and oceans was among the three highest in records dating to the mid- to late 1800s. In Europe, 17 countries reported record high annual mean temperatures, contributing to the warmest year on record for the European continent. Elsewhere, Japan, Mexico, and Seychelles also experienced re-cord high annual mean temperatures. In the Caribbean, Aruba, Martinique, and St. Lucia reported their all-time monthly maximum temperatures. In the United States, Furnace Creek in Death Valley, California, reached 54.4°C on 16 August—the hottest temperature measured on Earth since 1931, pending confirma-tion. North of 60°N, the annual mean temperature over Arctic land areas was 2.1°C above the 1981–2010 average, the highest in the 121-year record. On 20 June, a temperature of 38°C was observed at Verkhoyansk, Russia (67.6°N), provisionally the highest temperature ever measured within the Arctic Circle. Near the opposite pole, an atmospheric river—a long, nar-row region in the atmosphere that ...